2015
DOI: 10.2147/idr.s80677
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of mortality and Candida isolates of 75 patients with candidemia: a single hospital experience

Abstract: The mortality rate for candidemia is approximately 30%–60%. However, prognostic factors in patients with candidemia have not yet been elucidated in detail. The aim of the present study was to analyze prognostic factors for candidemia using the mortality rate and Candida isolates of patients with candidemia. Seventy-five patients with candidemia were analyzed between January 2007 and December 2013. The main outcome of this study was the 30-day mortality rate after the diagnosis of candidemia. The acute physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 22 publications
6
31
0
Order By: Relevance
“…As may be expected, fewer cases of haematological cancer or transplantation were found among elderly patients . These patients present a high index of suspicion of infection and early empirical antifungal therapy is frequently prescribed .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As may be expected, fewer cases of haematological cancer or transplantation were found among elderly patients . These patients present a high index of suspicion of infection and early empirical antifungal therapy is frequently prescribed .…”
Section: Discussionsupporting
confidence: 81%
“…These patients present a high index of suspicion of infection and early empirical antifungal therapy is frequently prescribed . In addition, the elderly patients in our series did not commonly present other risk factors, such as malignant neoplasm, ICU admission, central line or parenteral nutrition as detected in other similar studies . A study focused in elderly patient (defined as patients >65 years) parenteral nutrition, CVC and glycopeptide antibiotics were found to be the strongest risk factors for candidaemia .…”
Section: Discussionsupporting
confidence: 57%
“…Although C. albicans is reported as the main cause of candidaemia worldwide, several reports from India, indicated C. tropicalis as the most prevalent candidaemia‐causing species . Moreover, it has been shown that the species distribution can also vary on a regional scale and even on a local scale within the hospital …”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, various amounts of C. albicans were added to PB samples to simulate BSI, which in vivo are characterised by the presence of both extracellular and phagocytised yeasts 1 2 8. Each blood sample was analysed in the BC-6800 in different times.…”
Section: Methodsmentioning
confidence: 99%